Estado nutricional de pacientes candidatos à cirurgia colorretal - Geraldo, Carla Maria Zordan (2017)
Colorectal cancer (CRC) is a prevalent disease in Brazil and worldwide. It is treated with surgical indication, neoadjuvant therapies such as Chemotherapy and / or Radiotherapy. Thus in elective surgeries, the approach of the multidisciplinary team to improve the clinical condition of surgical patients is required. Nutritional impairments to the side effects of cancer treatment prior to surgery are permanent. Therefore, the preoperative nutritional assessment, therapy and post-surgical nutritional monitoring are fundamental, since this nutritional impairment contributes to the increase of postoperative morbidity and mortality. Objective: To identify the status and preoperative nutritional risk of patients eligible for colorectal surgery. Methods: We studied from February, 2014 to August, 2015, 22 patients (11 men and 11 women; 59.6± 12.4 years) hospitalized in the Coloproctology Department of Hospital de Base/ FAMERP candidates to the elective major abdominal surgery. Preoperative evaluation was performed by a protocol that comprised subjective global assessment (SGA), objective nutritional assessment (ONA), anthropometric parameters (weight, height, BMI, measures of circumferences and triceps skinfold), biochemical (hematocrit, hemoglobin and serum albumin) and dietary recall of the usual intake. Nutritional risk was calculated according to criteria combined according to the Nutritional Guidelines Nutritional Therapy (DITEN) and the Second National Consensus Oncology Nutrition (CNNO) based on parameters such as: weight loss (pp)>10% in 6 months, severe malnutrition according to SGA, BMI <18.5kg/m2 (adults) or 22 kg/m2 (elderly) and serum albumin <3.0g/dL. Results: In the study, 18 (81.8%) patients had cancer (50.0% colon cancer and 31.8% rectal cancer). All patients had major surgery indication, 8 (27.3%) reported having gastrointestinal symptoms, 20 (90.9%) reported no impairment in functional capacity and 8 (36.4%) showed depletion of adipose tissue and lean mass. Nine (40.9%) patients were considered malnourished or at nutritional risk according to SGA, and only 2 (9.1%) according to BMI (P=0.0339). Thirteen (59.1%) of them were overweighed according to BMI, 7 (31.8%) and 11 (50%) were classified with malnutrition / nutritional risk and overweight according to ONA, respectively. Regarding the anthropometric profile, the group of men towards women; higher weight median (77.8kg x 60.0 kg, P=0.0126), CMB (26.4 cm x 22.2 cm P=0.0372), DC (100 cm x 80 cm; P=0.0301) and WHR (0.99 x 0.88, P=0.0010) were observed. Regarding the PCT, there was a higher median in the female group compared to the group of men (23.0 mm x 10.0 mm; P=0.0065). In 10 (45.5%) patients and in 11 (50%) of them, the ingestion of calories and protein was smaller than 75% of the required. Only 2 (9.1%) patients had serum albumin levels between 3.5 and 3.0 g/dL. Thus, 4 (18.2%) patients were considered to have severe nutritional risk according to DITEN and II CNNO. Conclusions: Considering the results found in the study, it is concluded that the impaired nutritional status, either by depletion of lean body mass, as the overweight is a common finding in patients undergoing surgery for colorectal cancer. Severe nutritional risk is present in these patients, so the Preoperative Nutritional Therapy is fundamental and can provide better results in the elective surgeries.